Cryptogenic organising pneumonia an unusual presentation as solitary pulmonary nodule - Ramana Prasad; Kiran Kumar Reddy (Journal of Medical and Scientific Research, 2014)
Organizing pneumonia (OP) is well recognized, but the contexts in which it is encountered continue to increase. In parallel with an appreciation of new causes and associations of OP, increasing array of High-resolution computed tomography (HRCT) manifestations, an understanding of OP in the spectrum of lung injury and repair has evolved. Cryptogenic organising pneumonia (COP) presenting as solitary pulmonary nodule (SPN) is very unusual and this case of cryptogenic organising pneumonia is presented as solitary pulmonary nodule.